MULTIMODAL ANALYSIS OF WARDAH LIPSTICK ADVERTISEMENT - Raharjo, Aning Rustanti; Hidayat, Didin Nuruddin; Alek, Alek; Jalil, Nasifuddin (Elite : English and Literature Journal, 2020)
Advertising is utilized to promote certain products and attract the attention of potential customers to purchase the products. In this study, the researchers use advertisements broadcasted through an electronic form, namely Wardah lipstick advertisement. The advertisement is audiovisual, and the form of the message included sound and moving images. The analysis in this study used a semiotic approach and multimodal analysis focusing on multimodal systems, including aspects of linguistics, visual, audio, gestural, and location. This study used qualitative research methodology by applying a descriptive analysis in the research. The study found that this advertisement covers the five aspects of the multimodal semiotic system: linguistics, visuals, audio, gestural, and location. These five aspects are integrated to convey the core message in Wardah lipstick advertisement. Finally, this research found the meaning contained in an advertising message. The advertisement structure was also composed of verbal and visual text to persuade and affect buyers’ decisions.